The Reception of Gratitude in the Kupatan Munggah Gunung Menjuluk Tradition; A Living Qur’an Study in Sedayulawas Village - Alfiyah, Avif; Pratiwi, Intan (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
Although Living Qur’an studies have significantly expanded discussions on how Qur’anic values are enacted in Muslim ritual life, the field remains largely dominated by descriptive accounts that treat local traditions primarily as symbolic representations. Such approaches tend to overlook how Qur’anic meanings are actively negotiated, reconfigured, and sustained within communities undergoing social and institutional transformation. Addressing this limitation, the present study examines the reception of Qur’anic gratitude (shukr) in the Kupatan Munggah Gunung Menjuluk tradition as a dynamic and socially embedded religious practice in contemporary Javanese Islam. This study mobilizes the Living Qur’an framework as an analytical tool rather than a descriptive label by integrating it with Karl Mannheim’s sociology of knowledge. Through Mannheim’s tripartite model of meaning—objective, expressive, and documentary—the research investigates how gratitude operates simultaneously as a theological principle, a communal ethic, and a carrier of cultural memory. Drawing on ethnographic methods, including participant observation, in-depth interviews, and symbolic–narrative analysis, the study demonstrates that Qur’anic gratitude is not merely reproduced textually but is selectively articulated through culturally mediated ritual practices. The findings reveal that the Kupatan Munggah Gunung Menjuluk ritual functions as a site of negotiation between Qur’anic authority and local cultural logic, particularly as the practice becomes institutionalized through processes of festivalization. In this context, gratitude is rearticulated in ways that prioritize social cohesion, moral education, and collective identity, while simultaneously reshaping the religious meanings attached to the ritual. Theoretically, this study advances Living Qur’an scholarship by moving beyond ritual description toward an analysis of religious meaning production, and contributes to broader debates in Islamic studies and the anthropology of religion by demonstrating how Qur’anic values operate as living moral resources that are continuously negotiated and reconstituted within culturally mediated religious practices in contemporary Muslim societies.